2018
DOI: 10.3390/bdcc2030029
|View full text |Cite
|
Sign up to set email alerts
|

Recreating the Relationship between Subjective Wellbeing and Personality Using Machine Learning: An Investigation into Facebook Online Behaviours

Abstract: Abstract:The twenty-first century has delivered technological advances that allow researchers to utilise social media to predict personal traits and psychological constructs. This article aims to further our understanding of the relationship between subjective wellbeing (SWB) and the Five Factor Model (FFM) of personality by attempting to replicate the relationship using machine learning prediction models. Data from the myPersonality Project was used; with observed SWB scores derived from the Satisfaction With… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Although machine-inferred personality manifest domain scores also showed good convergent validity, discriminant validity was less impressive, particularly in the test sample. Nevertheless, overall, our results show improvements in differentiating among different traits in the machineinferred personalities as compared to existing machine learning applications (e.g., Hickman et al, 2022;Marinucci et al, 2018;Park et al, 2015). Table 7 also shows that C1, D1, and D2 (D2a) dropped around .10 from the training to testing sample at both the latent and manifest variable levels.…”
Section: Convergent and Discriminant Validitysupporting
confidence: 51%
See 1 more Smart Citation
“…Although machine-inferred personality manifest domain scores also showed good convergent validity, discriminant validity was less impressive, particularly in the test sample. Nevertheless, overall, our results show improvements in differentiating among different traits in the machineinferred personalities as compared to existing machine learning applications (e.g., Hickman et al, 2022;Marinucci et al, 2018;Park et al, 2015). Table 7 also shows that C1, D1, and D2 (D2a) dropped around .10 from the training to testing sample at both the latent and manifest variable levels.…”
Section: Convergent and Discriminant Validitysupporting
confidence: 51%
“…We identified four empirical studies that examined the discriminant validity of machineinferred personality scores (Harrison et al, 2019;Hickman et al, 2022;Marinucci et al, 2018;Park et al, 2015), with findings suggesting relatively poor discriminant validity. For instance, Park et al (2015) showed that the average correlations among Big Five domain scores were significantly higher when measured by the ML method than by self-report questionnaires (𝑟𝑟̅ = .29 vs. 𝑟𝑟̅ = .19).…”
Section: Discriminant Validitymentioning
confidence: 99%
“…Although machine-inferred personality manifest domain scores also showed good convergent validity, discriminant validity was less impressive, particularly in the test sample. Nevertheless, overall, our results show improvements in differentiating among different traits in the machine-inferred personalities as compared to existing machine learning applications (e.g., Hickman et al, 2022; Marinucci et al, 2018; Park et al, 2015). Table 7 also shows that C1, D1, and D2 (D2a) dropped around .10 from the training to testing sample at both the latent and manifest variable levels.…”
Section: Resultsmentioning
confidence: 59%
“…Another important finding is that the current study, which was based on self-report models, yielded better psychometric properties (e.g., substantially higher convergent validity and cross-sample generalizability) of machine-inferred personality scores than many similar ML studies that were also based on self-report models (e.g., Hickman et al, 2022;Marinucci et al, 2018). We offer several tentative explanations that might help reconcile this inconsistency.…”
Section: Important Findings and Implicationsmentioning
confidence: 61%
See 1 more Smart Citation